Radiobiology for the radiologist - Hall, Eric J.; Giaccia, Amato J. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2012)
"The seventh edition is the most radical revision of this textbook to date and now includes color figures, a visual transformation over the sixth edition. However, we were careful to retain the same format as the sixth edition, which divided the book into two parts. Part I contains 17 chapters and represents both a general introduction to radiation biology and a complete self-contained course in the subject, suitable for residents in diagnostic radiology and nuclear medicine. It follows the format of the Syllabus in Radiation Biology prepared by the Radiological Society of North America (RSNA), and its content reflects the questions appearing in recent years in the written examination for diagnostic radiology residents given by the American Board of Radiology. Part II consists of 11 chapters of more in-depth material designed primarily for residents in radiation oncology. We live in an exciting time, but yet a dangerous time as well. The threat of nuclear terror rears its head way too often. If such an event occurs, those trained in the radiation sciences will be called on to manage exposed individuals. For this reason, we have included a new chapter on Radiologic Terrorism (Chapter 14). The translation of molecular imaging into the clinic is moving at a rapid pace. Therefore, we also included a chapter on fundamental concepts in molecular imaging that involves ionizing radiation such as CAT scans and PET imaging to reflect these new advances and describe the underlying biologic principles for each of these technologies (Chapter 15). The subject of retreatment with radiotherapy is not covered in most textbooks, and, because of this void, we have dedicated a new chapter to this subject (Chapter 24)"--Provided by publisher.
Machine generated contents note: Section I: For Students of Diagnostic Radiology, Nuclear Medicine, and Radiation Oncology 1. Physics and Chemistry of Radiation Absorption 2. Molecular Mechanisms of DNA and Chromosome Damage and Repair 3. Cell Survival Curves 4. Radiosensitivity and Cell Age in the Mitotic Cycle 5. Fractionated Radiation and the Dose-Rate Effect 6. Oxygen Effect and Reoxygenation 7. Linear Energy Transfer and Relative Biologic Effectiveness 8. Acute Radiation Syndrome 9. Radioprotectors 10. Radiation Carcinogenesis 11. Heritable Effects of Radiation 12. Effects of Radiation on the Embryo and Fetus 13. Radiation Cataractogenesis 14. Radiological Terrorism 15. Molecular Imaging 16. Doses and Risks in Diagnostic Radiology, Interventional Radiology and Cardiology, and Nuclear Medicine 17. Radiation Protection Section II: For Students of Radiation Oncology 18. Cancer Biology 19. Dose-Response Relationships for Model Normal Tissues 20. Clinical Response of Normal Tissues 21. Model Tumor Systems 22. Cell, Tissue, and Tumor Kinetics 23. Time, Dose, and Fractionation in Radiotherapy 24. Retreatment after Radiotherapy: The Possibilities and the Perils. 25. Alternative Radiation Modalities 26. The Biology and Exploitation of Tumor Hypoxia 27. Chemotherapeutic Agents from the Perspective of the Radiation Biologist 28. Hyperthermia.
Includes bibliographical references and index
Keywords: Medical physics; Radiobiology; Radiology, Medical; Radiation Effects; Radiobiology; Radiotherapy